Product Form Identification Technology Based on Cognitive Thinking - Shutao Zhang; Jianning Su; Chibing Hu; Peng Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In this paper, based on the analyzing of the selecting and distinguishing characteristics of cognitive thinking, the product design elements are analyzed with the theories of Kansei Engineering, and the corresponding mathematic model for the analysis is developed based on the quantification-I theory to quantitatively discuss the relationship between product form design elements and the psychological kansei image of the users. With foregoing investigation result, practicable program software has been developed as a solver tool to subsequent design. Finally, a practical application of testing machine is presented, and the results show that the method is reasonable and feasible as well. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3422